1991
DOI: 10.3758/bf03205061
|View full text |Cite
|
Sign up to set email alerts
|

The syllable-length effect in number processing is task-dependent

Abstract: Two experiments were run in order to investigate the relationship between syllable length of number names and eye-fixation durations during silent reading of one-and two-digit numbers. In Experiment 1, subjects had to read a series of three numbers and recall them orally; in Experiment 2, subjects had to indicate manually whether the value of the middle number was between the values of the outer numbers. The effect of syllable length was controlled for possible confounding effects of number frequency and numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 27 publications
6
41
0
Order By: Relevance
“…10) that was similar to gaze duration times for single digit reading (Gielen, Bryzbaert, & Dhont, 1991). Some psychophysical studies have reported logarithmic behavior with respect to number magnitude, such as subitizing experiments (Mandler & Shebo, 1982) and two-digit number reading experiments (Bryzbaert, 1995).…”
Section: Discussion Of Where Processing Propertiesmentioning
confidence: 64%
See 2 more Smart Citations
“…10) that was similar to gaze duration times for single digit reading (Gielen, Bryzbaert, & Dhont, 1991). Some psychophysical studies have reported logarithmic behavior with respect to number magnitude, such as subitizing experiments (Mandler & Shebo, 1982) and two-digit number reading experiments (Bryzbaert, 1995).…”
Section: Discussion Of Where Processing Propertiesmentioning
confidence: 64%
“…In the experiments by Gielen, Bryzbaert, and Dhont (1991), the gaze duration is used to estimate the time interval needed by the subjects to process a numerical stimulus under no time stress. This interval ranged from 200 to 600 ms for one-digit and two-digit numbers.…”
Section: Discussion Of Where Processing Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The regressions indicated that the number of syllables and the numeral frequency, but not the number magnitude, determined the gaze durations, even when the contribution of the other factors was partialled out. However, the results by Gielen et al (1991) were contested in a follow-up study by Brysbaert (1995). When controlling for several methodological factors, such as lack of power and inclusion of the numeral 0, Brysbaert (1995) showed that gaze durations for numerals ranging from 1 to 99 were a function of the logarithm of magnitude.…”
mentioning
confidence: 99%
“…Pynte's stimuli differed not only in number of syllables but also in number magnitude and numeral frequency. In order to determine the contribution of all three factors, Gielen, Brysbaert, and Dhondt (1991) conducted multiple regression analyses on the gaze durations in the silent naming of all one-and two-digit arabic numerals ranging from 0 to 99. The regressions indicated that the number of syllables and the numeral frequency, but not the number magnitude, determined the gaze durations, even when the contribution of the other factors was partialled out.…”
mentioning
confidence: 99%